Investigating the relationship between formal and informal care: An application using panel data for people living together. (7th June 2019) - Urwin, Sean; Lau, Yiu‐Shing; Mason, Thomas
Abstract: There is limited evidence on the relationship between formal and informal care using panel data in a U.K. setting and focused specifically on people living together (co‐residents). Using all 18 waves of the British Household Panel Survey (1991–2009), we analyse the effect of informal care given by co‐residents on the use of formal home care and health care services more generally. To account for endogeneity, we estimate models using random effects instrumental variable regression using the number of daughters as a source of exogenous variation. We find that a 10% increase in the monthly provision of informal care hours decreases the probability of using home help (formal home care) by 1.02 percentage points ( p < .05), equivalent to a 15.62% relative reduction. This effect was larger for home help provided by the state ( β = −.117) compared with non‐state home help ( β = −.044). These results provide evidence that significant increases in the supply of informal care would reduce the demand for home‐help provision.